Physical activity moderates the association between white matter hyperintensity burden and cognitive change - Song, Suhang; Gaynor, Alexandra M.; Gazes, Yunglin; Lee, Seonjoo; Xu, Qianhui; Habeck, Christian; Stern, Yaakov; Gu, Yian (Frontiers in Aging Neuroscience, 2022)
Objective: Greater physical activity (PA) could delay cognitive decline, yet the underlying mechanisms remain unclear. White matter hyperintensity (WMH) burden is one of the key brain pathologies that have been shown to predict faster cognitive decline at a late age. One possible pathway is that PA may help maintain cognition by mitigating the detrimental effects of brain pathologies, like WMH, on cognitive change. This study aims to examine whether PA moderates the association between WMH burden and cognitive change. Methods: This population-based longitudinal study included 198 dementia-free adults aged 20-80 years. Leisure-time physical activity (LTPA) was assessed by a self-reported questionnaire. Occupational physical activity (OPA) was a factor score measuring the physical demands of each job. Total physical activity (TPA) was operationalized as the average of z-scores of LTPA and OPA. Outcome variables included five-year changes in global cognition and in four reference abilities (fluid reasoning, processing speed, memory, and vocabulary). Multivariable linear regression models were used to estimate the moderation effect of PA on the association between white matter hyperintensities and cognitive change, adjusting for age, sex, education, and baseline cognition. Results: Over approximately five years, global cognition (p<.001), reasoning (p<.001), speed (p<.001), and memory (p<.05) scores declined, and vocabulary (p<.001) increased. Higher WMH burden was correlated with more decline in global cognition (Spearman’s rho=-0.229, p=.001), reasoning (rho=-0.402, p<.001), and speed (rho=-0.319, p<.001), and less increase in vocabulary (rho=-0.316, p<.001). Greater TPA attenuated the association between WMH burden and changes in reasoning (βTPA*WMH=0.029, 95% CI=0.006-0.052, p=.013), speed (βTPA*WMH=0.035, 95% CI=-0.004-0.065, p=.028), and vocabulary (βTPA*WMH=0.034, 95% CI=0.004-0.065, p=.029). OPA seemed to be the factor that exerted a stronger moderation on the relationship between WMH burden and cognitive change. Conclusion: PA may help maintain reasoning, speed, and vocabulary abilities in face of WMH burden. The cognitive reserve potential of PA warrants further examination.